The influence of post-processing software on quantitative results in 4D flow cardiovascular magnetic resonance examinations - Trauzeddel, Ralf F.; Müller, Maximilian; Demir, Aylin; Wiesemann, Stephanie; Daud, Elias; Schmitter, Sebastian; Viezzer, Darian; Hadler, Thomas; Schulz-Menger, Jeanette (Frontiers in Cardiovascular Medicine, 2024)
Different commercially available software exist for the analysis of three-dimensional cine phasecontrast cardiovascular magnetic resonance (CMR) with three-directional velocity encoding (4D Flow CMR). There is only sparse data available on the impact of these different software solutions on quantitative results. We compared two different commercially available and widely used software and their impact on forward flow volume (FFV), peak velocity (PV) and maximum wall shear stress (WSS) per plane.4D Flow CMR datasets acquired at 3T of 10 healthy volunteers and 13 patients with aortic stenosis (AS) and 7 patients with aortic valve replacement (AVR) were retrospectively analyzed for FFV, PV and WSS using two software packages in six analysis planes along the thoracic aorta. Absolute (AD) and relative differences (RD), intraclass correlation coefficients (ICC) and Bland-Altman analysis as well as Spearman`s correlation analysis were calculated.For FFV and PV in healthy volunteers, there was good to excellent agreement between both software (FFV: ICC = 0.93 -0.97, AD: 0.1 ± 5.4 ml -(-2.3 ± 2.4 ml), RD: -0.3 ± 8 % -(-5.7 ± 6.0 %); PV: ICC = 0.81 -0.99, AD: -0.02 ± 0.02 ml -(-0.1 ± 0.1 ml), RD: -1.6 ± 2.1 % -(-9.3 ± 6.1 %)). In patients, FFV showed good to excellent agreement (ICC: 0.75 -0.91, AD: -1.8 ± 6.5 ml -(-8.3 ± 9.9 ml), RD: -2.2 ± 9.2% -(-13.8 ± 17.4 %)). PV in the ascending aorta showed only poor to moderate agreement in patients (Plane 2 ICC: 0.33, Plane 3 ICC: 0.72), whereas the rest of the thoracic aorta revealed good to excellent agreement (ICC: 0.95 -0.98, AD: -0.03 ± 0.07 -(-0.1 ± 0.1 m/s), RD: -3.5 ± 7.9% -(-7.8 ± 9.9%)). WSS analysis showed no to poor agreement between both software packages. Global correlation analyses revealed good to very good correlation between FFV and PV and only poor correlation for WSS.There was good to very good agreement for FFV and PV except for the ascending aorta in patients when comparing PV and no agreement for WSS. Standardization is therefore necessary.